2020
DOI: 10.1093/texcom/tgaa022
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal GABA Levels Correlate with Memory in Older Adults at High Risk for Alzheimer’s Disease

Abstract: γ-aminobutyric acid (GABA), primary inhibitory neurotransmitter in the brain, plays a significant role in aging and in neurodegenerative disorders, including Alzheimer’s disease (AD). We investigated the relationship between GABA levels in the dorsomedial/dorsoanterolateral prefrontal cortex (DM/DA-PFC) and memory in high-AD risk participants. Thirty-eight participants (14 Cognitively Normal (CN), 11 with Subjective Cognitive Decline, and 13 Mild Cognitive Impairment (MCI)) underwent magnetic resonance spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Its homeostasis regulates psychological manifestation. On the one hand, normal GABA levels inhibit neuronal hyper-excitability causing irritability, seizures, movement disorders, anxiety, insomnia, fatigue, and various psychiatric disorders; on the other hand, its excessive values cause sedation, sleepiness, and lethargy [ 76 , 77 , 78 ]. The synthesis of GABA depends on its major precursor, glutamate, forming a vital neurotransmitter cycle, namely the glutamate-glutamine-GABA cycle [ 20 ].…”
Section: Neuroimaging In the Cognitive Impairmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Its homeostasis regulates psychological manifestation. On the one hand, normal GABA levels inhibit neuronal hyper-excitability causing irritability, seizures, movement disorders, anxiety, insomnia, fatigue, and various psychiatric disorders; on the other hand, its excessive values cause sedation, sleepiness, and lethargy [ 76 , 77 , 78 ]. The synthesis of GABA depends on its major precursor, glutamate, forming a vital neurotransmitter cycle, namely the glutamate-glutamine-GABA cycle [ 20 ].…”
Section: Neuroimaging In the Cognitive Impairmentmentioning
confidence: 99%
“…However, the detection of GABA is complicated because of interactions between nuclei and signal overlapping, which can be overcome by several methods enabling its quantification, chiefly by Mescher–Garwood-editing of MRS [ 20 , 47 , 71 , 79 ]. Several studies have reported decreased GABA in AD, focusing on the temporal, frontal, and parietal lobes [ 50 , 77 ], although no significant GABA changes in AD compared with controls have been confirmed across the frontal lobe, hippocampus, and cingulate gyrus [ 50 , 71 ]. Since the brain regions of AD subjects show changes in Glx but not in GABA, ongoing asymmetric involvement of glutamatergic and GABAergic neurons or different rates of excitation-inhibition might occur in AD-affected cortical areas [ 80 , 81 ].…”
Section: Neuroimaging In the Cognitive Impairmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower cortical GABA levels are associated with worse global cognition, fluid processing, sensorimotor performance, and memory performance in normative aging (Porges et al, 2017; Simmonite et al, 2019; Cassady et al, 2019; Murari et al, 2020; Jiménez-Balado et al, 2021; reviewed in Li et al, 2022). However, few studies of cortical GABA levels have included oldest-old adults (85 years and older), and none have compared young-old and old-old adults (Porges et al, 2017; Simmonite et al, 2019).…”
Section: Introductionmentioning
confidence: 99%